Activated carbon assisted electrocoagulation process for treating biotreated palm oil mill effluent - Tahreen, Amina; Jami, Mohammed Saedi; Ali, Fathilah (2021)
Electrocoagulation (EC) is a sustainable wastewater treatment alternative that is widely studied because of its environmentally friendly nature, versatility, and simplicity in setup and operation. However, EC alone cannot treat wastewater up to reusable standards and requires integration with other processes, mostly by adding highly hazardous oxidants. This work aims to investigate the combination of powdered activated carbon (AC) with biotreated palm oil mill effluent (BPOME) as wastewater sample, in the EC reactor, and to optimize its concentration for maximum pollutant removal efficiency. Ranging from 0.5-1.5 wt. % concentration of AC mixed with EC reactor, EC was carried out with its critical parameters set to a current of 1.75 A (i.e., 160 mA/cm2 current density) and initial pH 6 and 10 mm interelectrode distance with aluminum electrodes. The EC treated wastewater was sampled from 5 minutes to 60 minutes and the parameters monitored were total suspended solids (TSS), turbidity, color and chemical oxygen demand (COD). Turbidity, TSS and color were removed nearly to completion within 5 to 15 minutes of EC, whereas maximum COD removal was determined to be 84.6 % with 1 wt. % powdered AC combined with EC, which is an increase of about 14.6% compared to EC with no AC addition. The optimum concentration of AC for maximum removal efficiency on BPOME was 1 wt. % (2 g per 200 ml). Addition of AC in EC resulted in a faster pollutant removal rate, with enhanced process efficiency.